2013
DOI: 10.1590/0074-0276130128
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of larval, ovitrap and MosquiTRAP surveillance for Aedes (Stegomyia) aegypti

Abstract: In Brazil, the entomological surveillance of Aedes (Stegomyia) aegypti is performed by government-mandated larval surveys. In this study, the sensitivities of an adult sticky trap and traditional surveillance methodologies were compared. The study was performed over a 12-week period in a residential neighbourhood of the municipality of Pedro Leopoldo, state of Minas Gerais, Brazil. An ovitrap and a MosquiTRAP were placed at opposite ends of each neighbourhood block (60 traps in total) and inspections were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 24 publications
(28 reference statements)
2
41
0
9
Order By: Relevance
“…aegypti abundance and serological data indicated that recent dengue infections were equally frequent in the intervention and control areas. The failure of the MosquiTRAP mass-trapping intervention may have resulted from its previously quantified poor performance relative to standard ovitraps (78.3% ovitraps positive for eggs vs. 46.4% MosquiTRAPs positive for adult females, p < 005, [53]) and the relatively low number of traps deployed per residence (three/house). More importantly, however, it is likely that the lack of pre-intervention source reduction campaigns also contributed to the poor performance of the relatively small MosquiTRAP due to competition from other water sources.…”
Section: Mass Lethal Ovitrapping Interventionsmentioning
confidence: 99%
“…aegypti abundance and serological data indicated that recent dengue infections were equally frequent in the intervention and control areas. The failure of the MosquiTRAP mass-trapping intervention may have resulted from its previously quantified poor performance relative to standard ovitraps (78.3% ovitraps positive for eggs vs. 46.4% MosquiTRAPs positive for adult females, p < 005, [53]) and the relatively low number of traps deployed per residence (three/house). More importantly, however, it is likely that the lack of pre-intervention source reduction campaigns also contributed to the poor performance of the relatively small MosquiTRAP due to competition from other water sources.…”
Section: Mass Lethal Ovitrapping Interventionsmentioning
confidence: 99%
“…The positivity index for each species of Culicidae was estimated by dividing the number of positive sampled axils for a given species by the total A. macrorrhizos axils investigated (Gomes 1998). The positivity index is usually used in studies with Culicidae and is important because it reveals the percentage frequency of occurrence of a particular species on the sampled sites throughout the investigated period (Resende et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Walaupun demikian, ovitrap tidak akan efektif lagi jika ditempatkan lebih dari 1 minggu karena bisa menjadi tempat perindukan nyamuk baru . Selain itu, indeks ovitrap dapat menjadi alternatif teknik yang digunakan dalam pengendalian vektor selain survei jentik karena metode ovitrap juga dapat mendeteksi nyamuk dari tempat perindukan yang tidak terjangkau dari area di sekitarnya (Beech et al 2009;de Resende et al 2013) Aedes sp. akan bertelur setelah menghisap darah dan jumlah telur rata-rata 100 butir setiap kali bertelur.…”
Section: Pendahuluanunclassified